Oleochemicals physical property data bank software (oleopro) - 301354 Robiah Yunus; Vasantharajan; Khairiyah Mohd. Yusof, 1965-; Symposium of Malaysian Chemical Engineers (12th : 1996 : Universiti Kebangsaan Malaysia, Bangi)
42